The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1508/cytologia.76.381
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Effects Induced by Methyl Methane Sulphonate in 2 Cultivars of <i>Capsicum annuum</i> L.

Abstract: Summary Seeds of Capsicum annuum L. cv. Pusa jwala and G 4 were treated with varying concentrations of methyl methane sulphonate (MMS), and the effect of various concentrations of MMS on each stage of meiosis has been studied in M1 generation. Various types of meiotic abnormalities and reduction in chiasma frequency were observed in treated populations. However, MMS treatment were found to be more effective in inducing meiotic abnormalities and reduction in chiasma frequency in Pusa jwala as compared to G 4 . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
3
1
0
Order By: Relevance
“…The fact that no significant increase in chromosome lagging and chromosome aberrations was seen in periods later than those observed, at concentrations of 10 and 15 mg/L in accession GF004 of bean (p ≥ 0.05), may be explained as being due to mitotic inhibition for an exposure period of 24 h, because the chromosome aberrations evaluated in this study require cells that are undergoing division to be noticed ( Rank, 2003 ). MMS is a clastogenic agent, and thus promotes chromosome breaks and the induction of chromosome lagging in plants, as previously reported in Capsicum annum L. ( Gulfishan et al , 2011 ; 2012 ) and Vicia faba L. ( Sharma et al , 2009 ) and also observed in the present study. In accession GF007, MMS did not produce a significant increase in the frequency of chromosome aberrations in the meristematic root cells, when compared with the control ( Table 4 ).…”
Section: Resultssupporting
confidence: 91%
“…The fact that no significant increase in chromosome lagging and chromosome aberrations was seen in periods later than those observed, at concentrations of 10 and 15 mg/L in accession GF004 of bean (p ≥ 0.05), may be explained as being due to mitotic inhibition for an exposure period of 24 h, because the chromosome aberrations evaluated in this study require cells that are undergoing division to be noticed ( Rank, 2003 ). MMS is a clastogenic agent, and thus promotes chromosome breaks and the induction of chromosome lagging in plants, as previously reported in Capsicum annum L. ( Gulfishan et al , 2011 ; 2012 ) and Vicia faba L. ( Sharma et al , 2009 ) and also observed in the present study. In accession GF007, MMS did not produce a significant increase in the frequency of chromosome aberrations in the meristematic root cells, when compared with the control ( Table 4 ).…”
Section: Resultssupporting
confidence: 91%
“…In this investigation, pollen fertility decreased with the increase in concentrations of the 5-BU. Similar decrease in pollen fertility was reported earlier in Vicia faba , Capsicum annuum (Gulfishan et al, 2010) and C. intybus . Reduction in pollen fertility also supports a decrease in seed production due to the meiotic anomalies.…”
Section: Discussionsupporting
confidence: 90%
“…Jayabalan and Rao (1987) suggested that stickiness might be due to disturbances in the cytochemically balanced reaction. Precocious movement of chromosome as observed during the present investigation, probably caused by spindle disfunction (Gulfishan et al 2010). Non-orientation and scattering of chromosomes at metaphase I was observed in the present investigation which may be due to either the inhibition of spindle formation or the destruction of spindle fibers (Kumar and Rai 2007).…”
Section: Resultssupporting
confidence: 67%